HUMAN RESOURCE MANAGEMENT AS AN EFFECTIVE EFFORT TO ACHIEVE COMPETITIVE ADVANTAGE IN COFFESHOP BUSINESSES - A. Nurul Asma Dini; Nuraeni Kadir; Fauziah Umar (Scientium Management Review, 2023)
Human Resource Management (HRM) has an important role in achieving competitive advantage in the coffeeshop business. This research identifies the important role of HR management in creating competitive advantage through several key aspects including HR planning, recruitment and selection, training and development, compensation and evaluation. Having qualified and competent employees is very important to be able to provide the best service for customers. By improving the ability of coffeeshop employees, in addition to being able to provide high-quality services, this will be an advantage to distinguish them from competitors. The method used in this research is descriptive qualitative with 4 research subjects. The result is that to achieve a competitive advantage, HR management must play an active role in managing human resources strategically. By doing good HR planning, proper recruitment and selection, employee development, and effective performance evaluation, the coffeeshop business can achieve a sustainable competitive advantage in this increasingly competitive market.